Comprehensive impacts of diversified cropping on soil health and sustainability. Issue 3 (16th March 2022) - Baldwin-Kordick, Rebecca; De, Mriganka; Lopez, Miriam D.; Liebman, Matt; Lauter, Nick; Marino, John; McDaniel, Marshall D.
ABSTRACT: Conventional agriculture in the Midwest US lacks diversity, relies heavily on external inputs to maintain crop yields, and contributes to soil and water quality degradation. Using diverse crop rotations and incorporating livestock are promising solutions to these and other problems linked to current cropping systems dominated by maize ( Zea mays L.) and soybean ( Glycine max (L.) Merr.). To better understand how agricultural diversification comprehensively affects soil health and function, we compared 20 soil health parameters linked to critical soil ecosystem services in 1) a conventional 2-year maize-soybean rotation, and 2) a diverse 4-year maize-soybean-oat ( Avena sativa L.)+alfalfa ( Medicago sativa L.)-alfalfa rotation that periodically received cattle manure. The strongest and most salient improvements in soil health from the diversified, 4-year cropping system included: 8% reduction in soil resistance to root growth ( p = .006), 16% increase in cation exchange capacity ( p = .001), 157% increase in salt-extractable soil carbon ( p = .024), and 62% increase in soil microbial biomass ( p = .017). These comprehensive improvements in general soil functioning coincided with enhanced crop yields, reduced requirement for agricultural inputs, and decreased environmental impacts – all while maintaining profitability. Despite declines in cropping system diversity globally, but especially in the Midwest US, these results provide strong evidence for the benefits of diversification.